The Correlation between Fiber Intake and Insulin Resistance in Normal and Overweight Employees in Jakarta - Santri Dwizamzami Faridahanum; Fariz Nurwidya; Yohannessa Wulandari (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aims to determine the correlation between fiber intake and insulin resistance in normal and overweight employees in Jakarta. This study is a cross-sectional study of 58 employees of a pharmacy company aged 19-49 years with normal or overweight and normal blood sugar. BMI, waist circumference, physical activity, smoking status and food intake were assessed. The fiber intake was assessed by 3 days estimated food record and the insulin resistance was assessed by HOMA IR obtained from fasting blood sugar and insulin. Data analysis technique used the Spearman Correlation test with the Statistical Package for Social Science (SPSS). Result obtained fiber intake and HOMA IR has r= -0.390 and p = 0.002. Based on the result of the study, it can be concluded that there is a negative correlation between fiber intake with insulin resistance in normal and overweight employees in Jakarta.